1990
DOI: 10.1111/j.1432-1033.1990.tb15480.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of neutral protease from Bacillus subtilis deduced from model‐building and limited proteolysis experiments

Abstract: The overall folding of neutral protease from Bacillus subtilis has been predicted by computer-aided modelling, taking as a basis the known three-dimensional structure of thermolysin. As expected from the 50% similarity of sequence between the two proteins, the structure of B. subtilis protease is similar to that of thermolysin, including the two-domain topology and location of elements of regular secondary structure (helices and strands), whereas specific differences were predicted in loop regions. A protrudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
(23 reference statements)
2
25
0
Order By: Relevance
“…Finally, the results reported here provide some insights into the partly folded TFE-state of proteins utilizing a proteolytic probe, and complement those obtained by other investigators using spectroscopic techniques (Buck et al, 1993(Buck et al, , 1995Alexandrescu et al, 1994;Shiraki et al, 1994;Schonbrunner et al, 1996). This study represents a continuation of our efforts to demonstrate that proteolytic enzymes can be used as reliable probes of protein structure and dynamics (Vita et al, 1985;Fontana et al, 1989Fontana et al, , 1993Signor et al, 1990;Polverino de Laureto et al, 1994a, 1994b, 1995a, 1995bVindigni et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, the results reported here provide some insights into the partly folded TFE-state of proteins utilizing a proteolytic probe, and complement those obtained by other investigators using spectroscopic techniques (Buck et al, 1993(Buck et al, , 1995Alexandrescu et al, 1994;Shiraki et al, 1994;Schonbrunner et al, 1996). This study represents a continuation of our efforts to demonstrate that proteolytic enzymes can be used as reliable probes of protein structure and dynamics (Vita et al, 1985;Fontana et al, 1989Fontana et al, , 1993Signor et al, 1990;Polverino de Laureto et al, 1994a, 1994b, 1995a, 1995bVindigni et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…The aim of the present work was to probe the conformational state of RNase when dissolved in aqueous TFE by using proteolytic enzymes as probes of protein structure and dynamics (Mihalyi, 1978;Neurath, 1980;Fontana et al, 1989Fontana et al, , 1993Price & Johnson, 1990;Signor et al, 1990;Wilson, 1991). This experimental approach relies on the fact that proteolysis of a polypeptide chain requires the binding of a chain segment of 6-8 amino acid residues of the polypeptide substrate at the active site cleft of the protease (Berger & Schechter, 1970).…”
mentioning
confidence: 99%
“…Indeed, the use of proteolytic enzymes as probes of protein structure and dynamics is a well recognized and often employed approach (Mihalyi, 1978 ;Neurath, 1980;Fontana et al, 1989Fontana et al, , 1993Signor et al, 1990). In analogy to all enzymic reactions, a proteolytic enzyme can cleave a polypeptide chain only if the site(s) of chain fission can bind and adapt to the specific stereochemistry of the enzyme active site.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that the specific or preferential fission of peptide bond(s) by limited proteolysis [11,12] is a useful procedure to probe structural and dynamic aspects of globular proteins [13][14][15][16][17]. A detailed analysis of the structural characteristics of the sites of specific cleavages in proteins allowed us to establish that native globular proteins are cleaved at exposed and flexible loops only and never at chain segments of regular secondary structure (helices) [13,16].…”
Section: Introductionmentioning
confidence: 99%